10 AN ANALYSIS OF PATIENTS' INTEREST IN RESEARCH FROM A MEMORY SPECIALTY CLINIC. (1st March 2005) - Lane, N. J.; Ohrt, T. L.; Meade, S. A.; Slattery, A. M.; Gleason, C. E.; Asthana, S.
Abstract : Purpose: Successful recruitment of subjects into clinical research trials is one of the most difficult tasks facing research centers. As the prevalence of many diseases continues to increase, the need for research into effective treatments and potential cures for these diseases has become critical. As the pressures of subject recruitment have accordingly reached a crucial level, it has become necessary to re-evaluate the potential resources for recruitment. One such resource for subject recruitment is specialty clinics whose primary focus is the disease under investigation. In order to achieve a practical estimation of the potential number of subjects to be enrolled, however, a realistic examination of the population that presents to specialty clinics of this nature is required. Methods: We performed an analysis on patient visits over the course of one year in a geriatric specialty memory clinic in Madison, Wisconsin. Results: Data revealed that the majority of patients (67%) who presented to this clinic were poor clinical research candidates. Reasons for consideration as a "poor candidate" include lack of evidence for a dementia diagnosis, transportation and/or caregiver burdens, severity of impairment, and comorbid medical conditions. Of the remaining clinic patients seen over the course of one year, 40% were eligible and interested in participating in research; however only 14% of the eligible population was enrolled into clinical research studies. Though this is higher than the 2002 CenterWatch Data, which stated that less than 10% of the eligible population of volunteers participate in clinical trials, it is a source of concern. Conclusions: Of those patients seen over one year in a dementia specialty clinic, only a small proportion was enrolled in clinical research. These findings have serious implications for the continued success of clinical trials, but may be aided by the development of a collaborative relationship between researchers and clinicians to foster a model forum for the presentation of research opportunities to eligible participants. Recommendations for the development of such networks will be addressed in detail.